Urinary Sodium Excretion, Blood Pressure, and Risk of Future Cardiovascular Disease and Mortality in Subjects Without Prior Cardiovascular Disease - Welsh, C.E.; Welsh, Paul; Jhund, Pardeep; Delles, Christian; Celis-Morales, C.; Lewsey, J.D.; Gray, S.; Lyall, D.; Iliodromiti, S.; Gill, J.M.R.; Sattar, Naveed; Mark, Patrick B. (Hypertension (Dallas, Tex. 1979), 2019)
Hypertension is a risk factor for cardiovascular disease. Increased urinary sodium excretion, representing dietary sodium intake, is associated with hypertension. Low sodium intake has been associated with increased mortality in observational studies. Further studies should assess whether confounding relationships explain associations between sodium intake and outcomes. We studied UK Biobank participants (n=457 484; mean age, 56.3 years; 44.7% men) with urinary electrolytes and blood pressure data. Estimated daily urinary sodium excretion was calculated using Kawasaki formulae. We analyzed associations between sodium excretion and blood pressure in subjects without cardiovascular disease, treated hypertension, or diabetes mellitus at baseline (n=322 624). We tested relationships between sodium excretion, incidence of fatal and nonfatal cardiovascular disease, heart failure, and mortality. Subjects in higher quintiles of sodium excretion were younger, with more men and higher body mass index. There was a linear relationship between increasing urinary sodium excretion and blood pressure. During median follow-up of 6.99 years, there were 11 932 deaths (1125 cardiovascular deaths) with 10 717 nonfatal cardiovascular events. There was no relationship between quintile of sodium excretion and outcomes. These relationships were unchanged after adjustment for comorbidity or excluding subjects with events during the first 2 years follow-up. No differing risk of incident heart failure (1174 events) existed across sodium excretion quintiles. Urinary sodium excretion correlates with elevated blood pressure in subjects at low cardiovascular risk. No pattern of increased cardiovascular disease, heart failure, or mortality risk was demonstrated with either high or low sodium intake.